Estimating daily net radiation in the FAO Penman - Monteith method - Carmona, Facundo (2016)
In this work, we evaluate the procedures of the Manual No. 56 of the FAO (United Nations Food and Agriculture Organization) for predicting daily net radiation using measures collected in Tandil (Argentina) between March 2007 and June 2010. In addition, a new methodology is proposed for estimating daily net radiation over the reference crop considered in the FAO Penman?Monteith method. The calculated and observed values of daily net radiation are compared. Estimation errors are reduced from ±22 to ±12 W m−2 considering the new model. From spring?summer data, estimation errors of less than ±10 % were observed for the new physical model, which represents an error of just ±0.4 mm d−1 for computing reference evapotranspiration. The new model presented here is not restricted to a climate regime and is mainly appropriate for application in the FAO Penman?Monteith method to determine the reference crop evapotranspiration.